Why Does the Epistle to the Hebrews Evoke the Desires of the Patriarchs? - Malina, Artur (Collectanea Theologica, 2021)
The Pontifical Biblical Commission’s document The Jewish People and their Sacred Scriptures in the Christian Bible, calls attention to a threefold connection between the two parts of the Christian Bible: continuity, discontinuity, and newness. The paper offers an analysis of a passage as an example of this relationship. The Epistle to the Hebrews (11:8–22) gives a particular emphasis to the desires of the patriarchs among other attitudes of the heroes of faith. They were looking for what was promised to them and desired by them: a city with the solid foundations planned and built by God. Now these desires can be fulfilled: the everlasting life with God is offered to all who believe in Jesus Christ.